Characterization of an olfactometer by proton-transfer reaction mass spectrometry. - Beauchamp, Jonathan; Frasnelli, Johannes; Büttner, Andrea; Scheibel, Markus; Hansel, Armin; Hummel, Thomas (Measurement Science and Technology, 2010)
The performance of a commercial olfactometer instrument, which produces odorant pulses of defined duration and concentration, was characterized using proton-transfer-reaction mass spectrometry (PTR-MS). Direct coupling of the PTR-MS instrument with the olfactometer enabled on-line evaluation of the rapidly delivered aroma pulses. Tests were made with a selection of four odorous compounds: hydrogen sulfide, 2,3-butanedione, ethyl butanoate and ethyl hexanoate. Odour concentrations and stimulus durations for these compounds were monitored directly at the olfactometer delivery port via the respective PTR-MS signals. The performance of the olfactometer was found to be dependent on pulse duration. A decrease over time in maximum intensity for identical pulses over an extended duration showed headspace concentration depletions for compounds sourced from a water solution, indicative of gas/liquid partitioning. Such changes were not present using odours sourced from a cylinder or, presumably, when using liquid odours at neat concentrations. In conclusion, while an olfactometer provides stimuli with good reproducibility, the concept is subject to certain limitations that must be appreciated by the experimenter for accurate application of this technique.<br